Recurrent Context Window Networks for Italian Named Entity Recognizer - Daniele Bonadiman (Accademia University Press, 2016)
In this paper, we introduce a Deep Neural Network (DNN) for engineering Named Entity Recognizers (NERs) in Italian. Our network uses a sliding window of word contexts to predict tags. It relies on a simple word-level log-likelihood as a cost function and uses a new recurrent feedback mechanism to ensure that the dependencies between the output tags are properly modeled. These choices make our network simple and computationally efficient. Unlike previous best NERs for Italian, our model does not require manual-designed features, external parsers or additional resources. The evaluation on the Evalita 2009 benchmark shows that our DNN performs on par with the best NERs, outperforming the state of the art when gazetteer features are used.